The Alteration of Intrinsic Excitability and Synaptic Transmission in Lumbar Spinal Motor Neurons and Interneurons of Severe Spinal Muscular Atrophy Mice - Sun, Jianli; Harrington, Melissa A. (Frontiers in Cellular Neuroscience, 2019)
Spinal muscular atrophy (SMA) is the leading genetic cause of death in infants. Studies with mouse models have demonstrated increased excitability and loss of afferent proprioceptive synapses on motor neurons. To further understand functional changes in the motor neural network occurring in SMA, we studied the intrinsic excitability and synaptic transmission of both motor neurons and interneurons from ventral horn in the lumbar spinal cord in the SMNΔ7 mouse model. We found significant differences in the membrane properties of motor neurons (MNs) in SMA mice compared to littermate controls, including hyperpolarized resting membrane potential, increased input resistance and decreased membrane capacitance. Action potential (AP) properties in MNs from SMA mice were also different from controls, including decreased rheobase current, increased amplitude and increased afterdepolarization potential. The relationship between AP firing frequency and injected current was reduced in MNs, as was the threshold current, while the percentage of MNs showing long-lasting potentiation in the intrinsic excitability was higher in SMA mice. Interneurons (INs) showed a high rate of spontaneous firing, and those from SMA mice fired at higher frequency. INs from SMA mice showed little difference in their input-output relationship, threshold current, and plasticity in intrinsic excitability. The changes observed in both passive membrane and AP properties suggest greater overall excitability in both MNs and INs in SMA mice, with MNs showing more differences. There were also changes of synaptic currents in SMA mice. The average charge transfer per post-synaptic current of spontaneous excitatory and inhibitory synaptic currents (sEPSCs/sIPSCs) were lower in SMA MNs, while in INs sIPSC frequency was higher. Strikingly in light of the known loss of excitatory synapses on MNs, there was no difference in sEPSC frequency in MNs from SMA mice compared to controls. For miniature synaptic currents, mEPSC frequency was higher in SMA MNs, while for SMA INs, both mEPSC and mIPSC frequencies were higher. In SMA-affected mice we observed alterations of intrinsic and synaptic properties in both MNs and INs in the spinal motor network that may contribute to the pathophysiology, or alternatively, may be a compensatory response to preserve network function.